A Mixed Integer Linear Programming Based Scheduling Model for Cost Minimization in Sea Tollway Vessel Operations - Jauza Ananda Ayuniar; Yuliani Puji Astuti (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
The Sea Tollway Program plays a critical role in Indonesia’s national logistics system by improving maritime connectivity and reducing regional disparities in goods distribution. However, operational inefficiencies in vessel scheduling and prolonged berthing times continue to limit its effectiveness. This study addresses these challenges by formulating a deterministic Mixed Integer Linear Programming (MILP) based vessel scheduling model with capacity and cargo flow constraints aimed at minimizing time-dependent operational cost and improving berthing time efficiency. A case study is conducted on Sea Tollway Route H-1 using operational data from the first semester of 2025. The optimization model is implemented using the PuLP library and solved with the CBC solver. The results show that the optimized schedules consistently reduce operational costs by approximately 5–8% per voyage and decrease berthing time by about 12–17%, corresponding to an average reduction of two hours per voyage. Statistical significance testing confirms that these improvements are not due to random variation, while sensitivity analysis demonstrates the robustness of the optimized solutions under changes in key operational parameters. Overall, the proposed MILP-based framework provides a mathematically sound and practically applicable decision-support tool for improving vessel scheduling and operational efficiency in Sea Tollway maritime logistics.